2019
DOI: 10.1155/2019/8982147
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine Attenuates Autophagy in Osteoclasts via an Axis of mROS/TRPML1/TFEB to Reduce LPS-Induced Bone Loss

Abstract: Lycorine, a plant alkaloid, exhibits anti-inflammatory activity by acting in macrophages that share precursor cells with osteoclasts (OCs). We hypothesized that lycorine might decrease bone loss by acting in OCs after lipopolysaccharide (LPS) stimulation, since OCs play a main role in LPS-induced bone loss. Microcomputerized tomography (μCT) analysis revealed that lycorine attenuated LPS-induced bone loss in mice. In vivo tartrate-resistant acid phosphatase (TRAP) staining showed that increased surface area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Protein extraction, separation by SDS-PAGE, transfer to nitrocellulose membranes, blocking, incubation with secondary antibodies, and development were performed as previously described [10]. Primary antibodies against phospho-IKKα/β (S176/180) (#2697, Cell Signaling, Danvers, MA, USA), lamin B (#13435, Cell Signaling), p65 (sc-372, Santa Cruz Biotechnology, Santa Cruz, CA, USA), PP2A (sc-13600, Santa Cruz Biotechnology), and β-actin (A5441, Sigma-Aldrich) were incubated with the membranes overnight at 4 • C.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Protein extraction, separation by SDS-PAGE, transfer to nitrocellulose membranes, blocking, incubation with secondary antibodies, and development were performed as previously described [10]. Primary antibodies against phospho-IKKα/β (S176/180) (#2697, Cell Signaling, Danvers, MA, USA), lamin B (#13435, Cell Signaling), p65 (sc-372, Santa Cruz Biotechnology, Santa Cruz, CA, USA), PP2A (sc-13600, Santa Cruz Biotechnology), and β-actin (A5441, Sigma-Aldrich) were incubated with the membranes overnight at 4 • C.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The fluorescent probe 2',7'-dichlorofluorescein diacetate (H 2 DCFDA) (Thermo Fisher Scientific, Waltham, MA, USA) and the Mito-SOX red mitochondrial superoxide indicator (Invitrogen, Carlsbad, CA, USA) were used to evaluate intracellular ROS and mitochondrial ROS, respectively, as described [10].…”
Section: Determination Of Intracellular and Mitochondrial Reactive Oxmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that drugs that inhibit inflammation and oxidation effectively attenuated lung damage, including astaxanthin, cordycepin, and linarin (Bi et al 2017 ; Han et al 2018 ; Lei et al 2018 ). Lycorine has been reported to be an effective inhibitor of tumor development and also had many other benefits, including reducing LPS-induced bone loss in mice and inhibiting intervertebral disc degeneration (Park et al 2019 ; Wang et al 2018 ). Here, we found that lycorine alleviated lung injury and inhibited pulmonary edema, inflammatory response, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…e inhibitory effect is stronger than that of dexamethasone. In addition, lycorine can also inhibit the production of PGE2 and IL-6 in macrophages to play an antipyretic and analgesic role [37].…”
Section: Lycorinementioning
confidence: 99%